2007
DOI: 10.1111/j.1558-5646.2007.00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Pleiotropy: Differential Epistasis as a Source of Variation in the Allometric Relationship Between Long Bone Lengths and Body Weight

Abstract: Pleiotropy is an aspect of genetic architecture underlying the phenotypic covariance structure. The presence of genetic variation in pleiotropy is necessary for natural selection to shape patterns of covariation between traits. We examined the contribution of differential epistasis to variation in the intertrait relationship and the nature of this variation. Genetic variation in pleiotropy was revealed by mapping quantitative trait loci (QTLs) affecting the allometry of mouse limb and tail length relative to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
146
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(160 citation statements)
references
References 42 publications
5
146
0
9
Order By: Relevance
“…At the phenotypic level, selection for compatible trait values of functionally and developmentally related traits is predicted to cause their co-inheritance and hence their genetic and phenotypic correlation (Olsen and Miller 1958;Lande 1980;Cheverud 1982Cheverud , 1984. More recently, Cheverud and colleagues (Cheverud et al 2004;Pavlicev et al 2007;Wagner et al 2007) have suggested that pleiotropic relationships should reflect the coselection of traits such that pleiotropic effects would be favored among traits selected together and not favored among traits selected independently. Our analysis of the relationship between pleiotropy and phenotypic correlation indicates that these two measures of trait relationship are relatively strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…At the phenotypic level, selection for compatible trait values of functionally and developmentally related traits is predicted to cause their co-inheritance and hence their genetic and phenotypic correlation (Olsen and Miller 1958;Lande 1980;Cheverud 1982Cheverud , 1984. More recently, Cheverud and colleagues (Cheverud et al 2004;Pavlicev et al 2007;Wagner et al 2007) have suggested that pleiotropic relationships should reflect the coselection of traits such that pleiotropic effects would be favored among traits selected together and not favored among traits selected independently. Our analysis of the relationship between pleiotropy and phenotypic correlation indicates that these two measures of trait relationship are relatively strongly correlated.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, statistical approaches have been applied to inbred cross data and typically find evidence for pleiotropy, for example, as in studies of weight and morphometry (Brockmann et al 2000;Leamy et al 2002;Wolf et al 2005Wolf et al , 2006Pavlicev et al 2008). However, these methods leave open the possibility that pleiotropy at a locus is attributable to multiple genes of different function that happen to reside next to each on the genome.…”
Section: Genetic Architecture: Pleiotropymentioning
confidence: 99%
“…2000; Pavlicev et al. 2008; Wagner and Zhang 2011). This conflict between selection and the maintenance of genetic variation in multiple traits remains a fundamental and puzzling problem in evolutionary biology (Walsh and Blows 2009).…”
mentioning
confidence: 99%
“…20052006; Pavlicev et al. 2008). Simulations using the information that epistatic interactions can provide variation in pleiotropy and covariance patterns have shown how selection can promote changes in pleiotropy that can change covariation (Jones et al.…”
mentioning
confidence: 99%